First record of Tempskya corda of Mulichinco formation (Valanginian), Sierra De La Vaca Muerta, Neuquén Basin, Argentina - Martinez, Leandro Carlos Alcides (2012)
The Mulichinco Formation (Valanginian) in Sierra de la Vaca Muerta (Neuquén province, Argentina) is mainly a clastic unit of a 50 to 150 meters thick sequence of conglomerates, sandstones and claystones that represents terrestrial to shallow marine deposits of a low-frequency lowstand wedge. Some of the sandstones are fluvial in origin and contain coniferous fossil woods and false trunks of Tempskya Corda, associated with dinosaur remains. In this contribution false trunks of Tempskya are described. They are silicified and consist of a system of solenostelic stems, dichotomously branching, and surrounded by a dense mat of adventitious roots. The genus Tempskya is an extinct fern preserved as permineralized false-trunks, with a global distribution during the Early Cretaceous. However, the records in the Southern Hemisphere are scarce, and restricted to the Rayoso Formation (Aptian - Albian, Neuquén Province, Argentina) and the Winton Formation (Albian, Queensland, Australia). This evidence from the Valanginian of Patagonia would represent the oldest record of Tempskya. The presence of this genus implies humid and warm climatic conditions during the deposition of the Mulichinco Formation.